Penicillin-resistant Variants of Pneumococci - Gunnison, Janet B. (1968)
All of the 74 strains of pneumococci isolated from human infections from 1963 to 1964 proved to be uniformly and highly susceptible to penicillin. Of these strains, 15 were identified by capsule-swelling reactions and were submitted to serial transfer in the presence of increasing concentrations of penicillin. Highly penicillin-resistant mutants were selected from 14 of the 15 strains, whereas one strain was moderately resistant. Of these mutants, 11 could still react with specific antiserum, and all of the mutants could be identified by fermentation reactions and optochin inhibition. The in vitro development of penicillin resistance in these mutants did not result in a change in cell-wall composition sufficient to diminish bile solubility. The possibility of encountering rising penicillin resistance among pneumococci, as well as the possibility that such mutants may react atypically, should be kept in mind.